The phenomenological nature of corruption - A complex, perennial and destabilizing event of social and political relations - Sbardellotto, Fabio Roque (Seven Editora, 2023)
This article proposes to explore the phenomenon of corruption, from its historical and conceptual perspective, to highlight its deleterious and perennial effects on the economy, politics, institutions, and society. The problematization presupposes evaluating the different philosophical, sociological, and legal approaches to the term corruption, demonstrating that, despite its difficult definition, in essence, it presupposes the degeneration of values, distorting nature and human development. In all its aspects, corruption is a pejorative and harmful phenomenon, derogatory of objects and beings, and corrosive of the values inherent to the common good. In this context, it is proposed to verify that, being a phenomenon, corruption permanently expands its effects, destabilizing and weakening institutions, at the same time that it foments levels of instability in society that impede human development, generating hostility, polarization, and fragility in social, economic, legal and political relations. DOI:https://doi.org/ 10.56238/devopinterscie-214